The Economy of Conflict in the Oil Rich Niger Delta Region of Nigeria (Nordic Journal of African Studies, 2005)
Economies of war underpinned by greed and opportunities have been posited to underlie causality, dynamics and the sustenance of conflicts and particularly Africa’s resource wars. The study examines the economy of conflict in the resource conflicts in the Niger Delta region of Nigeria. It was found that a conflict economy comprising an intensive and violent struggle for resource opportunities, inter and intra communal/ethnic conflicts over resources and the theft and trading in refined and crude oil has blossomed since the 1990s. The paper examines the interfaces between the Nigerian state, multi-national oil companies, the international community and youth militias with the economy.It was found that though the economy did not cause the conflict, it has become a part of the resistance and a resource for sustaining it. The economy underpins an extensive proliferation of arms and the institutions of violence and the pervasiveness of crime, violence and communal/ethnic conflicts.